A Review of the Effects of Self-Service Technologies on Firm Performance in Kenya - Juma Adhaya , Zedekia; Ochieng Odock, Stephen (Multidisciplinary Journal of Technical University of Mombasa, 2021)
Self-service technology (SST) continues to create tremendous impact on the business environment globally. A technology that allows consumers to take on the traditional place of service agents in the provision of services. Business organizations are taking advantage of the advancement in technology to improve service delivery and performance. The advancement in technology particularly with respect to nanotechnology, genome sequencing and artificial intelligence are among the drivers of the 4th Industrial Revolution. Consequently, information technology advancement is changing the marketing landscape of goods and services such that service industry, notably hospitality and transport have increased the prevalence of SSTs, as critical drivers of an organization’s industrial strength level. By a firm adopting technology-based strategy, this means higher clients’ satisfaction, cost minimization, and faster accurate service delivery with higher consistency among other benefits. This paper therefore, assesses the impact of SSTs and emphasizes on actual adoption and usage of self-service as proposed by technology acceptance model. The study reviews theoretical and empirical literature on the subject of SSTs and firm performance, identifies the research gaps and puts forward a suitable conceptual framework that can investigate the link between SST and firm performance. This paper uses secondary data to establish research gaps and the determinant of the success of adoption of SST by a firm. From a total of 54 articles reviewed, almost all studies on SSTs are based on the service sector focusing least on the internal customers in Kenya. A few studies related directly to the performance of the firms to the adoption of SSTs. Agricultural and manufacturing sectors particularly in the rural areas are unexploited directly. This is due to infrastructural imbalances in the urban and rural areas. The outcome of this review would enlighten; administrators of firms in Kenya and the entire East African region on the importance of ICT infrastructure, the information resources and the strategies for optimizing electronic services to attain competitive advantage. It widens the frontiers of knowledge for the academic community in production and operation management and enhances the understanding of the customer SST interactions in different industries. It creates further valuable implications on the industrial sectors, principally to the managers who use the information in drafting service related strategies and hence become a yardstick to evaluate the present service initiatives appropriately. It allows the managers to have a basis to determine whether the massive investment in adoption of technology is justifiable. Finally, this paper contributes to the existing knowledge in self-service technology and customer satisfaction and serves as source of reference to future researchers and academicians in this field.